2016
DOI: 10.1111/jse.12187
|View full text |Cite
|
Sign up to set email alerts
|

A molecular phylogeny of Chinese orchids

Abstract: We estimated the molecular phylogenetic relationships of the Chinese members of the family Orchidaceae. Within the Tree of Life for the Genera of Chinese Vascular Plants using atpB, rbcL, matK, ndhF, and matR, the currently delimited subfamilies, tribes, and subtribes are highly supported as monophyletic except for the perplexing Epidendroideae. Five genes (rbcL, matK, psaB, ycf1, and Xdh), which are more universally used in Orchidaceae, were further analyzed to reconstruct the phylogeny of Epidendroideae. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 68 publications
(150 reference statements)
3
31
0
Order By: Relevance
“…Morphologically, Odontochilus is distinguished from Anoectochilus by its saccate and non-extruded spur enclosed by the lateral sepals and two parallel stigma lobes positioned under the rostellum, whereas Anoectochilus has a conical spur extruded beyond the lateral sepals and two remote stigma lobes (Lin and Hsu 1976, Pridgeon et al 2003, Chen et al 2009, Pedersen et al 2011). Recent results of molecular systematics indicated that Odontochilus is closely related to Chamaegastrodia and Rhomboda , whereas Anoectochilus is closely related to Ludisia (Li et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Morphologically, Odontochilus is distinguished from Anoectochilus by its saccate and non-extruded spur enclosed by the lateral sepals and two parallel stigma lobes positioned under the rostellum, whereas Anoectochilus has a conical spur extruded beyond the lateral sepals and two remote stigma lobes (Lin and Hsu 1976, Pridgeon et al 2003, Chen et al 2009, Pedersen et al 2011). Recent results of molecular systematics indicated that Odontochilus is closely related to Chamaegastrodia and Rhomboda , whereas Anoectochilus is closely related to Ludisia (Li et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…and Neottieae Lindl.) in subfamily Epidendroideae were selected as ingroup, while two species from subfamily Orchidoideae as outgroup according to the updated molecular phylogeny of Orchidaceae (Chase et al 2015;Li et al 2016). All the sequences were downloaded from NCBI GenBank and aligned using MAFFT v7.307 (Katoh and Standley 2013).…”
mentioning
confidence: 99%
“…Phylogenetic analysis based on 79 protein-coding genes of 10 representative plastomes within the subfamily Epidendroideae as ingroup. According to the updated molecular phylogeny of Orchidaceae (Chase et al 2015;Li et al 2016), 10 species from two tribes (Malaxideae Lindl. and Arethuseae Lindl.)…”
mentioning
confidence: 99%